Analisis Kemampuan Komunikasi Matematis Siswa Pada Materi Program Linear - Muhammad Rizal Usman; Andi Rifaq Guttu Patalo; Djadir Djadir (Jurnal Edukasi dan Sains Matematika (JES-MAT), 2021)
This research aims to analyze the mathematical communication ability of class XI students of SMA Negeri 1 Pangkep on the linear program material. This research is a qualitative research. The research procedure includes the preparation stage, the implementation stage, and the data analysis stage. The selection of research subjects was carried out by looking at the students' academic mathematics scores, namely the highest, medium, and lowest scores in the class swith the KKM score as a reference for assessment. The instruments used are tests of mathematical communication ability and interviews. Checking the validity of the data used was the triangulation technique. The results showed that the students of class XI Mathematics and Natural Sciences lacked an understanding of the Linear Program material so that the students had low mathematical communication skills in the Linear Program material.